A Truncated Singleton NLR Causes Hybrid Necrosis in Arabidopsis thaliana. (23rd September 2020) - Barragan, Ana Cristina; Collenberg, Maximilian; Wang, Jinge; Lee, Rachelle R Q; Cher, Wei Yuan; Rabanal, Fernando A; Ashkenazy, Haim; Weigel, Detlef; Chae, Eunyoung
Abstract: Hybrid necrosis in plants arises from conflict between divergent alleles of immunity genes contributed by different parents, resulting in autoimmunity. We investigate a severe hybrid necrosis case in Arabidopsis thaliana, where the hybrid does not develop past the cotyledon stage and dies 3 weeks after sowing. Massive transcriptional changes take place in the hybrid, including the upregulation of most NLR (nucleotide-binding site leucine-rich repeat) disease-resistance genes. This is due to an incompatible interaction between the singleton TIR-NLR gene DANGEROUS MIX 10 ( DM10 ), which was recently relocated from a larger NLR cluster, and an unlinked locus, DANGEROUS MIX 11 ( DM11 ). There are multiple DM10 allelic variants in the global A. thaliana population, several of which have premature stop codons. One of these, which has a truncated LRR–PL (leucine-rich repeat [LRR]–post-LRR) region, corresponds to the DM10 risk allele. The DM10 locus and the adjacent genomic region in the risk allele carriers are highly differentiated from those in the nonrisk carriers in the global A. thaliana population, suggesting that this allele became geographically widespread only relatively recently. The DM11 risk allele is much rarer and found only in two accessions from southwestern Spain—a region from which the DM10 risk haplotype is absent—indicating that the ranges of DM10 and DM11 risk alleles may be nonoverlapping.